Perancangan Sistem Informasi Manajemen Aplikasi Pendaftaran Rekening Bank Baru Nasabah - Tengku Syahvina Rival Dini; Puji Sri Alhirani; Mhd.Furqan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research was designed using Unified Modeling Language (UML) as a tool for visualizing system requirements. The system designed is expected to improve efficiency, accuracy and speed of service, thereby providing a better experience for customers and making it easier for Bank Sumut officers to manage registration data. The system development method used is waterfall. The research results show that the designed information system can automate various manual processes such as collecting prospective customer data, document validation, and managing account data. It is hoped that this management information system can be used to provide an overview of the applications that will be created to increase the Bank's operational productivity and minimize the potential for administrative errors, as well as supporting the digital transformation of Bank North Sumatra in facing competition in the banking sector.